2013
DOI: 10.1080/09593330.2012.722691
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of aqueous pharmaceuticals by pulsed corona discharge

Abstract: Oxidation of aromatic compounds of phenolic (paracetamol, beta-oestradiol and salicylic acid) and carboxylic (indomethacin and ibuprofen) structure used in pharmaceutics was studied. Aqueous solutions were treated with pulsed corona discharge (PCD) as a means for advanced oxidation. Pulse repetition frequency, delivered energy dose and oxidation media were the main parameters studied for their influence on the process energy efficiency. The PCD treatment appeared to be effective in oxidation of the target comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 23 publications
1
31
0
Order By: Relevance
“…[28,29,39], and it has been well known that inorganic ions such as NO 3 À , NH 4 + and SO 4 2À are generated by cleavages of bonds containing N and S atoms during the oxidation treatment [19,40,41]. The toxicity of degradation byproducts may be a matter of concern.…”
Section: Degradation Productsmentioning
confidence: 98%
See 1 more Smart Citation
“…[28,29,39], and it has been well known that inorganic ions such as NO 3 À , NH 4 + and SO 4 2À are generated by cleavages of bonds containing N and S atoms during the oxidation treatment [19,40,41]. The toxicity of degradation byproducts may be a matter of concern.…”
Section: Degradation Productsmentioning
confidence: 98%
“…They found that among various reactive species ozone played a major role in the degradation of antibiotics. Pulsed corona discharge plasma as a means for advanced oxidation has also been applied to the oxidation of aqueous pharmaceuticals [28,29]. The authors reported that this method is effective in the oxidation of pharmaceuticals and ultimate oxidation byproducts are low-molecular carboxylic acids.…”
Section: Introductionmentioning
confidence: 98%
“…[2] The increased production and use of UV filters has led to increased inputs into the environment and this fact prompted UV filters to be considered environmental pollutants in the same group of emerging pollutants classified as pharmaceuticals and personal care products. [3][4][5][6][7] UV filters may enter the environment through direct and indirect *Corresponding author. Email: jcsilva@fc.up.pt sources.…”
Section: Introductionmentioning
confidence: 99%
“…[20,21] Hazard quotient effects of paracetamol were determined to be greater than unity suggesting potential ecological risks [22] and it is persistent on hydrolytic or microbial degradation. [23] Paracetamol is removed from water by several ways which include ozonation, [24] [24,25] photocatalytic degradation, [26][27][28][29][30] electrochemical methods, [31][32][33] pulsed corona discharge [34] and chlorination. [19] Paracetamol is mainly removed from water using such methods but persistent toxic intermediates are still present.…”
Section: Introductionmentioning
confidence: 99%